Vascular Smooth Muscle Sirtuin‐1 Protects Against Aortic Dissection During Angiotensin II–Induced Hypertension. Issue 9 (16th September 2015) - Fry, Jessica L.; Shiraishi, Yasunaga; Turcotte, Raphaël; Yu, Xunjie; Gao, Yuan Z.; Akiki, Rachid; Bachschmid, Markus; Zhang, Yanhang; Morgan, Kathleen G.; Cohen, Richard A.; Seta, Francesca
Abstract : Background: Sirtuin‐1 (SirT1), a nicotinamide adenine dinucleotide + –dependent deacetylase, is a key enzyme in the cellular response to metabolic, inflammatory, and oxidative stresses; however, the role of endogenous SirT1 in the vasculature has not been fully elucidated. Our goal was to evaluate the role of vascular smooth muscle SirT1 in the physiological response of the aortic wall to angiotensin II, a potent hypertrophic, oxidant, and inflammatory stimulus. Methods and Results: Mice lacking SirT1 in vascular smooth muscle (ie, smooth muscle SirT1 knockout) had drastically high mortality (70%) caused by aortic dissection after angiotensin II infusion (1 mg/kg per day) but not after an equipotent dose of norepinephrine, despite comparable blood pressure increases. Smooth muscle SirT1 knockout mice did not show any abnormal aortic morphology or blood pressure compared with wild‐type littermates. Nonetheless, in response to angiotensin II, aortas from smooth muscle SirT1 knockout mice had severely disorganized elastic lamellae with frequent elastin breaks, increased oxidant production, and aortic stiffness compared with angiotensin II–treated wild‐type mice. Matrix metalloproteinase expression and activity were increased in the aortas of angiotensin II–treated smooth muscle SirT1 knockout mice and were prevented in mice overexpressing SirT1 in vascular smooth muscle or with use of the oxidant scavenger tempol. Conclusions: Endogenous SirT1 in aortic smooth muscle is required to maintain the structural integrity of the aortic wall in response to oxidant and inflammatory stimuli, at least in part, by suppressing oxidant‐induced matrix metalloproteinase activity. SirT1 activators could potentially be a novel therapeutic approach to prevent aortic dissection and rupture in patients at risk, such as those with hypertension or genetic disorders, such as Marfan's syndrome.